Like a Lost Route in a No-Man’s Land: Dilruba Z. Ara’s Journey into the Psyche of the Expatriate (Erothanatos: A Peer-Reviewed Quarterly Journal on Literature, 2021)
Dilruba Z. Ara is an internationally acclaimed Bangladeshi author based in Sweden. Ara’s collection of short stories in Detached Belonging―which contains other stories along with the one titled ‘Detached Belonging’―brings out the anguish and agony of protagonists ofmainly Bangladeshi cultures living in Sweden. This article explores the ways in which these protagonists negotiate their identities while living in what  Ara herself calls a ‘no-man’s land’ (Ara 10) in one of her stories. At the same time, the stories also depict scenarios of confronting one’s own cultural norms which is a consequence of hybridisation (Bhaba) and cultural alienation. This article also aims at exploring how and for what purpose the Bangladeshi variety of English used sometimes by the writer, blends in effortlessly with the standard variety and how the loss of verbal language altogether contributes to playing a key factor in the breakdown of communication which further contributes to the cultural alienation. Language and silences in this collection of short stories is a means of re-claiming one’s identity as well as a tool for negotiating between different cultures.
Keywords: cross-cultural negotiation; post-human society; mode of becoming; reterritorialisation; alienation